2015
DOI: 10.14723/tmrsj.40.211
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Photoinduced and Reversible Sol-Gel Conversions of Polymer Materials Containing Photoreactive Coumarin Moieties

Abstract: Hydrophilic copolymers containing N-isopropylacrylamide and acrylate with coumarin or 4-methylcoumarin moieties have been synthesized. We reveal that the copolymers with a very small content of coumarin and 4-methylcoumarin units exhibit macroscopic photoinduced and reversible sol-gel conversions. UV light (λ>310 nm) irradiation of aqueous solutions for the copolymers causes the increase in viscosity and the formation of hydrogels, based on photodimerization of coumarin moieties. Subsequent irradiation with UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In particular, some coumarin derivatives cause a photoinduced cyclodimerization [152,153] to a cyclobutane-based dimer. The reverse process (photocleavage) can be induced upon irradiation with higher energy photons (wavelength = 254 nm) [154][155][156][157][158]. Cheng-Mei Liu et al have reported that photodimerization of coumarin was first investigated by Ciamician and Silber [159].The dimerized product showed a melting point of 262°C [160], much higher than the original coumarin"s melting temperature of 68-70 °C.…”
Section: Coumarin Based Polymersmentioning
confidence: 99%
“…In particular, some coumarin derivatives cause a photoinduced cyclodimerization [152,153] to a cyclobutane-based dimer. The reverse process (photocleavage) can be induced upon irradiation with higher energy photons (wavelength = 254 nm) [154][155][156][157][158]. Cheng-Mei Liu et al have reported that photodimerization of coumarin was first investigated by Ciamician and Silber [159].The dimerized product showed a melting point of 262°C [160], much higher than the original coumarin"s melting temperature of 68-70 °C.…”
Section: Coumarin Based Polymersmentioning
confidence: 99%